FRI0342 Does exclusion of the ESR from JADAS affect validity in the clinical setting in assessment of new-onset juvenile inflammatory arthritis?. (23rd January 2014) - Mcerlane, F.; Beresford, M.W.; Baildam, E.M.; Chieng, S.E.; Davidson, J.; Foster, H.E.; Gardner-Medwin, J.; Lunt, M.; Wedderburn, L.R.; Hyrich, K.L.; Thomson, W.
Abstract : Background: Juvenile Arthritis Disease Activity Score (JADAS) is a 4 variable composite disease activity (DAS) score for juvenile idiopathic arthritis (JIA), including active 10, 27 or 71 joint count (AJC), physician global (PGA), parent/child global (PGE) and ESR. We have shown in previous work that the ESR is not routinely assessed in all patients with JIA; this reduces the feasibility of JADAS use in clinical practice. Objectives: To determine whether exclusion of the ESR from JADAS (labelled JADAS3 followed by 10, 27 or 71 respectively) influences correlation with single markers of disease activity (DA), in a prospective inception cohort of UK children presenting with new onset inflammatory arthritis. Methods: The JADAS 10, 27 and 71 and JADAS3-10, -27 and -71 were determined for all children in the Childhood Arthritis Prospective Study (CAPS) with complete data available at baseline. Correlation of JADAS 71 and JADAS3-71 with single markers of DA was determined for all ILAR subtypes (Spearman's rank statistic). Results: 354/1041 (34%) children had all four variables and 562/1041 (54%) children had three variables (ie without ESR) available at baseline. 994 (95%) had AJC available, 811 (78%) PGA, 694 (67%) PGE and 647 (62%) ESR. Median age at disease onset was 6.8 years (IQR 2.8-10.8), median disease duration at diagnosis was 5.2 mths (IQR 2.5-10.9) and 64% were female. Correlation for the whole cohort between JADAS3-71 and both JADAS3-27 and -10 was 0.99. Median JADAS3-71 ranged from 5.9-16.7/91 across the subtypes (Table 1 ). Correlation of JADAS 71 with JADAS3-71 was high, both for the whole cohort (0.96) and within individual ILAR subtypes (range 0.91 to 0.99). Correlation of JADAS 71 and JADAS3-71 with single markers of DA was similar between subtypes with the exception of the ESR; this may simply be a reflection of the variation in the frequency of measurement of the ESR between subgroups. Conclusions: Correlation of single DA markers with JADAS3-71 was moderate to good across all ILAR subtypes. JADAS3 is potentially a valid surrogate for JADAS in the clinical setting when the ESR is unavailable. Further validation studies are required to determine whether JADAS and JADAS3 reflect changes in DA over time. Disclosure of Interest: None Declared